An assessment of interventions that target risk factors for elder abuse. (22nd February 2016) - Day, Andrew; Boni, Nadia; Evert, Helen; Knight, Tess
Abstract: Although there is increasing concern about both the prevalence of, and harms associated with the abuse of older adults, progress in the development of interventions to prevent its occurrence has been slow. This paper reports the findings of a systematic review of the published literature that identified studies in which the outcomes of preventative interventions are described. A total of eight different intervention trials, published since 2004, are described across the primary, secondary and tertiary levels of prevention and in terms of the types of risk factor that they target. The current evidence to support the effectiveness of these interventions is not only limited by the small number of outcome studies but also the poor quality of evaluation designs and the focus of many interventions on single risk factors. It is concluded that work is needed to strengthen the evidence base that supports the delivery of interventions to prevent elder abuse.